Signature of Coordination Defects in the Vibrational Spectrum of Amorphous Chalcogenides - Micoulaut, Matthieu; Boolchand, Punit (Frontiers in Materials, 2019)
Using model structures obtained from molecular dynamics simulations, we calculate the Infrared absorption spectrum of amorphous and liquid As$_2$Se$_3$. The calculated spectrum is in rather good good agreement with the experimental counterpart and contains the signatures of coordination defects represented by quasi-tetrahedral Se=AsSe$_{3/2}$ units which dominate the vibrational spectrum beyond 300 cm$^{-1}$ with a typical vibration for the As=Se bond near 370~cm$^{-1}$. Conversely, the most prominent peaks around 100 and 200 cm$^{-1}$ are mainly due to vibrations of As atoms in pyramidal geometry. The study of the thermal behavior indicates that such defects increase with temperature so that their presence in the glass is reminiscent of the liquid state. They are, furthermore, metastable in character, as are other defects such as 1- and 3-fold Se, and relax to a few percent on the picosecond timescale once an instantaneous quench has been achieved from high temperature to room temperature.